2022
DOI: 10.1186/s40317-021-00272-w
|View full text |Cite
|
Sign up to set email alerts
|

Environmental correlates of activity and energetics in a wide-ranging social carnivore

Abstract: Background Environmental conditions can influence animal movements, determining when and how much animals move. Yet few studies have quantified how abiotic environmental factors (e.g., ambient temperature, snow depth, precipitation) may affect the activity patterns and metabolic demands of wide-ranging large predators. We demonstrate the utility of accelerometers in combination with more traditional GPS telemetry to measure energy expenditure, ranging patterns, and movement ecology of 5 gray wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 129 publications
0
12
2
Order By: Relevance
“…This nding was in contrast to Bryce et al (2022), who noted the energetic costs derived from accelerometers tted to wolves were on average 1.3 times higher than the GPS method. Discrepancies between our results and that of Bryce et al (2022) are likely due to differences in ecology between wolves and brown bears, and highlight the importance of species-speci c considerations when examining GPS-derived energetic expenditure. Our movement based energetic expenditures (2.7-8.9 J kg -1 s -1 ) were similar to ranges for grizzly bears in the Yellowstone ecosystem, with reported expenditure values of 3.0-10.6 J kg -1 s -1 (Carnahan et al 2021).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This nding was in contrast to Bryce et al (2022), who noted the energetic costs derived from accelerometers tted to wolves were on average 1.3 times higher than the GPS method. Discrepancies between our results and that of Bryce et al (2022) are likely due to differences in ecology between wolves and brown bears, and highlight the importance of species-speci c considerations when examining GPS-derived energetic expenditure. Our movement based energetic expenditures (2.7-8.9 J kg -1 s -1 ) were similar to ranges for grizzly bears in the Yellowstone ecosystem, with reported expenditure values of 3.0-10.6 J kg -1 s -1 (Carnahan et al 2021).…”
Section: Discussioncontrasting
confidence: 72%
“…Consent for publication may only be suitable for comparisons of movement-based energy expenditure among individuals (Bryce et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…Altering the time budgets from more profitable activities (foraging, resting) to increased vigilance after disturbance may have fitness costs (Ordiz et al, 2013). Therefore, quantifying how human activities can affect carnivore behavior, and the potential implications for energy budgets (e.g., Bryce et al, 2022), can elucidate the role of wilderness areas for large carnivore conservation (Gilroy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Accelerometers are also data intensive due to their continuous high frequency measurements, making analysis computationally demanding. A GPS-derived measure of energy expenditure offers an alternative to study animal energetic ecology when accelerometer data may not be available (Carnahan et al 2021;Bryce et al 2022). We found that the GPS-derived estimates of MDEE were on average 1.6 times greater than the ACC method, displayed less overall variation and likely overestimated true energetic expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Carnahan et al 2021). However, this method cannot account for metabolic energy demands and may only be suitable for comparisons of movement-based energy expenditure among individuals(Bryce et al (2022).…”
mentioning
confidence: 99%